Analysis of load taps changer performance under balanced supply using simulation and experimental results - (:unkn) unknown (My University, 2012)
An on-load tap-changer (OLTC) is indispensable operating equipment for the regulation of power transformers in energy supplying networks. The importance of on-load tap-changers has steadily been increasing with the years. Today, almost all generator-type transformer and power transformers are equipped with on-load tap-changers. Not only is this similarly true for networks of all other industrial states, but also does the energy supply in developing countries more and more ask for regulated power transformers. It can generally be stated that an increase in the density and link of a network goes together with an increase in the necessity for the regulation transformer. In this study; after giving a brief about the type of high speed resistor on-load tap-changers, the process of changing a tapchanger has been modeled in Matlab Simulink environment. In order to verify the simulation results, the process of changing a tap changer has been repeated in the laboratory by using Crozet brand of PLC. The experimental data has been transferred to PC through the Tektronix brand 4-channel digital oscilloscope. The data obtained here has verified the tap changer model. Then a new model has been created by combining the tap changer model and the power transformer. This model has been simulated again under balanced processing conditions in Matlab Simulank environment and current-voltage changes of a phase of the system which is during the transition are discussed. © Sila Science.
Keywords: OLTC experimental results; OLTC simulation; On-load taps changers